2018
DOI: 10.1159/000491670
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 Inhibits Tumor Cell Migration via Regulating Cell Surface Morphology in Non-Small Cell Lung Cancer Cells

Abstract: Background/Aims: Cell surface morphology plays pivotal roles in malignant progression and epithelial-mesenchymal transition (EMT). Previous research demonstrated that microvilli play a key role in cell migration of non-small cell lung cancer (NSCLC). In this study, we report that Forkhead box class O1 (FOXO1) is downregulated in human NSCLC and that silencing of FOXO1 is associated with the invasive stage of tumor progression. Methods: The cell proliferation, migration, and invasion were characterized in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…The cell skeleton which regulates cell polarity and morphology plays an essential role in cell migration and adhesion as well. In our study, morphological analysis after staining with crystal violet shows that cells are elongated, and cell shapes are correlated with migration status [23,24], in a concentration-dependent manner from 5 to 25 μM ( Fig. 2a).…”
Section: Silibinin Promotes Migration Of C2c12 Myoblasts In a Concentsupporting
confidence: 51%
“…The cell skeleton which regulates cell polarity and morphology plays an essential role in cell migration and adhesion as well. In our study, morphological analysis after staining with crystal violet shows that cells are elongated, and cell shapes are correlated with migration status [23,24], in a concentration-dependent manner from 5 to 25 μM ( Fig. 2a).…”
Section: Silibinin Promotes Migration Of C2c12 Myoblasts In a Concentsupporting
confidence: 51%
“…Epigenetic regulation, especially phosphorylation by AKT serine/threonine kinase (Akt), could promote its degradation and dysfunction [6]. Importantly, FoxO factors have been identified as tumour suppressors involved in the biological behaviours of cancer cells, such as extracellular matrix degradation, angiogenesis and migration [7][8][9]. FoxO factors are involved in regulating the genes associated with cellular cycle progression and inducing apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…FoxO1 negatively regulates the growth of lung cancer tumor cells in mice [44]. Increased FoxO3 expression enhances radiation resistance in NSCLC cells [45]. This study found that the active ingredients of Shenlian Capsule act on 17 proteins related to the FoxO signaling pathway.…”
Section: Discussionmentioning
confidence: 72%